Workplace aggression against healthcare workers in a Spanish healthcare institution between 2019 and 2021: The impact of the COVID-19 pandemic - Díaz, Aitor; Utzet, Mireia; Mirabent, Joan; Diaz, Pilar; Ramada, Jose Maria; Serra, Consol; Benavides, Fernando G. (Frontiers in Public Health, 2023)
Objectives Describe the incidence of first aggressions among healthcare workers (HCWs) before and during the COVID-19 pandemic in a Spanish healthcare institution, according to workers’ socio-occupational characteristics and analyze the impact of the pandemic on it. Methods Retrospective cohort from January 1, 2019 to December 31, 2021 of HCWs working in the institution for at least 1 week each year. Adjusted relative risks (aRR) between periods were estimated with generalized estimating equations negative binomial models. All analyses were sex-stratified. Results The incidence was 6.8% (6.0; 7.8) during the pre-COVID-19 period, 6.0% (5.2; 7.0) during the COVID-19 baseline and 5.1% (4.3; 5.9) during the COVID-19 endline among women, and 4.6% (3.4; 6.1), 5.3% (4.1; 6.8) and 4.4% (3.5; 5.8), respectively, among men. These incidences were significantly higher among male nurses and aides (11.1% (8.0; 15.4), 12.3% (8.9; 16.6), and 9.3% (6.5; 13.3) each period) and psychiatric center workers (women: 14.7% (11.2; 19.0), 15.4 (11.8; 19.8), and 12.4% (9.2; 16.6); men: 12.3% (7.2; 20.0), 17.8% (11.6; 26.2), and 14.3% (8.8; 22.4)). Women showed a risk of aggression during the COVID-19 endline 23% lower than before the pandemic (aRR=0.77 (0.64; 0.93)), while the risk during the COVID-19 baseline was not different (aRR=0.89 (0.74; 1.06)). Conclusions The COVID-19 pandemic led to an unexpected decrease in first aggressions against HCWs. However, around 5% of HCWs experienced at least one aggression in the last follow-up year. Healthcare managers should continue to increase prevention of aggressions against HCWs, especially among vulnerable groups with a higher incidence.